Pengaruh Pariwisata Halal terhadap Pendapatan Daerah pada 10 Provinsi Destinasi Wisata Halal Indonesia (Lembaga Pengembangan Kinerja Dosen, 2025)
Halal tourism is a specialized segment of the travel business that offers services that are in line with sharia or Islamic principles to meet the demand of Muslim tourists. With a large Muslim population and increasing demand for halal tourist locations around the world, halal tourism in Indonesia has great potential for economic growth. However, despite this potential, Indonesia still faces challenges in fully realizing its capacity in the halal tourism sector. Therefore, Indonesia is currently advancing the idea of halal tourism in ten provinces through the Ministry of Tourism and Creative Economy. The purpose of this study is to present data on how halal tourism affects regional income in 10 provinces of halal tourism locations in Indonesia. This study uses a quantitative methodology. With secondary data and panel data regression analysis, which combines data from 2017 to 2023 with provincial data covering 10 provinces in Indonesia that are developing halal tourism sourced from BPS, KEMENPAREKRAF, MINISTRY OF FINANCE, SIMREG, BAPPENAS, as well as the tourism office website in each region that is a Halal tourist destination. The findings of the study show that the Number of Muslim Tourism, the Number of Services and Facilities, and the Number of Tourist Destinations both partially and simultaneously, do not show a significant influence on regional income.